2014
DOI: 10.1002/ijc.29190
|View full text |Cite
|
Sign up to set email alerts
|

T cell‐based targeted immunotherapies for patients with multiple myeloma

Abstract: Despite high-dose chemotherapy followed by autologs stem-cell transplantation as well as novel therapeutic agents, multiple myeloma (MM) remains incurable. Following the general trend towards personalized therapy, targeted immunotherapy as a new approach in the therapy of MM has emerged. Better progression-free survival and overall survival after tandem autologs/ allogeneic stem cell transplantation suggest a graft versus myeloma effect strongly supporting the usefulness of immunological therapies for MM patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 205 publications
(203 reference statements)
0
9
0
Order By: Relevance
“…We identified 73 different HLA ligands representing 22 of 25 (88%) previously described myeloma antigens. 42 We found 9 of the 22 detectable antigens (41%) to be exclusively presented on MM samples, 10 of 22 antigens (45.5%) to be represented both on MM and HV samples, and 3 of 22 (13.6%) exclusively presented on HV-derived samples ( Figure 3A). Of note, 7 of 9 MMexclusive antigens (77.8%) were only detectable on MCLs.…”
Section: Blood 3 September 2015 X Volume 126 Number 10 T-cell Epitomentioning
confidence: 76%
See 2 more Smart Citations
“…We identified 73 different HLA ligands representing 22 of 25 (88%) previously described myeloma antigens. 42 We found 9 of the 22 detectable antigens (41%) to be exclusively presented on MM samples, 10 of 22 antigens (45.5%) to be represented both on MM and HV samples, and 3 of 22 (13.6%) exclusively presented on HV-derived samples ( Figure 3A). Of note, 7 of 9 MMexclusive antigens (77.8%) were only detectable on MCLs.…”
Section: Blood 3 September 2015 X Volume 126 Number 10 T-cell Epitomentioning
confidence: 76%
“…[25][26][27][28][29][30][31][32][33][34][35] However, these studies were limited in scope of antigens and HLA allotypes. 42 In our previous studies in acute myeloid leukemia and chronic lymphocytic leukemia, we demonstrated that the comprehensive and comparative analysis of the HLA-presented antigenome can identify extensive panels of broadly presented T-cell epitopes covering a multitude of HLA allotypes. 12,13 Here, we translated this systematic approach to MM.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therapeutic monoclonal antibodies (mAbs) such as IPH2101 comprise just one dimension (28) of the promising, rapidly expanding field of immunotherapy for MM which also includes NK- and T-cellular therapies (29,30), vaccines (30) and immunomodulating agents, among others. Tumor-directed mAbs (31,32) as well as effector cell-targeted mAbs (21,22,33) provide an opportunity for increasing precision with which to modulate immunity against MM, as well.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although sclerostin null mice have high bone mineral density, they have increased B-cell apoptosis due to decreased osteoblast-derived CXCL12, resulting from increased Wnt signaling [71]. Moreover, although the immune system in general suppresses multiple myeloma [72], not all immune cells mediate this role. Regulatory T-cells and immunosuppressive myeloid-derived suppressor cells [73] are now being identified as important new targets that inhibit the immune response in multiple myeloma [74].…”
Section: Effects Of Osteoblasts On Multiple Myelomamentioning
confidence: 99%